The trading of economists and the construction of a "market" symbolic order - Lebaron, Frédéric (Universidade Estadual de Campinas, UNICAMP, Unidade da Faculdade de Ciências Aplicadas de Limeira-SP, vinculada ao Laboratório de Estudos do Setor Público, LESP, 2012)
The training of economists, wether "professionals" (within universities, public administration, professional organizations or businesses) or simply "economics graduates" (in various sectors: primarily in the bank, finance and administration) contributes to the construction of a symbolic order centered on the market. Through its action, the market becomes an obvious social reality and is constructed as quasi-natural - its "laws" are seen as necessary by all social actors, political actors in particular - ; it is formatted symbolically and promoted by the actors of a scientific discipline which socializes the dominant players, and it serves, from now on, as the universe of reference for political institutions, administrative and economic.